"Guide" of muscone modification enhanced brain‐targeting efficacy and anti‐glioma effect of lactoferrin modified DTX liposomes. Issue 2 (18th August 2022) - Qi, Na; Duan, Wenjuan; Gao, Duan; Ma, Ningzhu; Zhang, Jianguo; Feng, Jianfang; Li, Aimin
Abstract: Glioma is one of the most aggressive malignant diseases for human health. It is difficult to resect completely due to their invasiveness. The targeted delivery, as a noninvasive approach, is a major strategy for the development of treatments for brain tumors. Lactoferrin (Lf) receptors are over‐expressed in both brain endothelial cells and glioma cells. Macromolecular Lf modified nanoparticles have been shown to enhance the brain targeting. Muscone is a "guide" drug that have been demonstrated to promote liposomes into the brain by modification. To further enhance the brain‐targeting efficacy of Lf modified carriers, we designed that Lf and muscone dual‐modified liposomes cross blood–brain barrier (BBB) and target to brain for enhanced docetaxel (DTX) brain delivery. The results showed that we successfully prepared Lf and muscone dual‐modified liposomes (Lf‐LP‐Mu‐DTX), the number of Lf molecules connected to the surface of per liposome was 28. Lf‐LP‐Mu‐DTX increased uptake in both U87‐MG cells and hCMEC/D3 cells, enhanced penetration of U87‐MG tumor spheroid and in vitro BBB model, had better in vitro and in vivo anti‐tumor effects. In conclusion, "guide" of muscone modification enhanced brain‐targeting efficacy of Lf modified liposomes, Lf and muscone dual‐modified docetaxel loaded liposomes present a potential brain‐targeting drug delivery system for use in the future treatment of gliomas.